Crossroad77 of the Bread of Life Ministries a study of the space planning of a christian community center - Fernandez, Anna Theresa Jauregui
The Christian church or community has recognized the need to adapt to the changes in the 21st century. This study attempts to evaluate how one particular Christian community, the Bread of Life Ministries, tried to address the needs of its members through its infrastructure known as Crossroad77. The space planning of Crossroad77 is examined to determine whether the different facilities of the building meet the various needs of the community. The methods used in the study include field research and survey. The researcher used her personal observations as well as covert active participation in some of the activities of the community. The primary source of information is the designing architect. A survey was conducted among the members regarding their point of view towards Crossroad77. Analysis of the data gathered from the survey showed a high satisfaction rate on the physical lay-out of Crossroad77. The field evaluation measures allowed a greater understanding of the functional relationship between the facilities and the activities and ministries of the community. Some recommendations were presented to further increase awareness and utilization of the facilities, safety and accessibility in the building. Over-all, the space planning of Crossroad77 building is able to support the physical needs and activities and ministries of the community.